(untitled) (Journal of the Bangladesh Agricultural University, 2014)
A total of 52 fecal samples were collected from 21 herbivores at Dhaka zoo during January to May, 2012 to investigate the prevalence of gastrointestinal parasites of herbivores. Overall prevalence of parasitic infection was 76.9%, of which 61.5% were positive for helminths and 55.8% were positive for protozoa. The identified parasites were Balantidium coli (55.8%), Paramphistomum sp. (36.5%), Fasciola sp. (19.2%), stomach worm (3.9%), Ascaris sp. (1.9%) and Strongyloides sp. (1.9%). Overall prevalence of mixed infection was 42.3%. Mixed infection was observed in the animals such as Butani cattle (Balantidium coli and Paramphistomum sp.), Giraffe (Balantidium coli and Paramphistomum sp.), Spotted deer (Balantidium coli, Paramphistomum sp. and Fasciola sp.), Sambar deer (Balantidium coli and Fasciola sp.), Horse (Balantidium coli and Ascaris sp.), Greater kudu (Balantidium coli and Paramphistomum sp.), Nil gai (Balantidium coli and stomach worm), Black wilde beast (Balantidium coli and Paramphistomum sp.), Impala (Balantidium coli and Strongyloides sp.), Hippopotamus (Balantidium coli and Paramphistomum sp.), Zebra (Balantidium coli and Paramphistomum sp.), Wilde beast (Balantidium coli and Paramphistomum sp.; Balantidium coli and Paramphistomum sp. and Fasciola sp.), One Horned Rhinoceros (Balantidium coli and Paramphistomum sp.), Common Eland (Balantidium coli and Paramphistomum sp.), Oryx (Balantidium coli and stomach worm). Diameter of ova or cyst was also measured. Egg per gram/ Cyst per gram of feces (EPG/ CPG) were ranged from 300-1200. Gastrointestinal parasites are highly prevalent in herbivores of Dhaka zoo. Strategic control measure is necessary to protect the endangered species from parasitic infestation. DOI: http://dx.doi.org/10.3329/jbau.v12i1.21245 J. Bangladesh Agril. Univ. 12(1): 79-85, June 2014